Exporting Through Intermediaries : Impact on Export Dynamics and Welfare - Kamali, Parisa (Washington, D.C. : International Monetary Fund, 2019)
In many countries, a sizable share of international trade is carried out by intermediaries. While large firms tend to export to foreign markets directly, smaller firms typically export via intermediaries (indirect exporting). I document a set of facts that characterize the dynamic nature of indirect exporting using firm-level data from Vietnam and develop a dynamic trade model with both direct and indirect exporting modes and customer accumulation. The model is calibrated to match the dynamic moments of the data. The calibration yields fixed costs of indirect exporting that are less than a third of those of direct exporting, the variable costs of indirect exporting are twice higher, and demand for the indirectly exported products grows more slowly. Decomposing the gains from indirect and direct exporting, I find that 18 percent of the gains from trade in Vietnam are generated by indirect exporters. Finally, I demonstrate that a dynamic model that excludes the indirect exporting channel will overstate the welfare gains associated with trade liberalization by a factor of two.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet